Deficiency of primate-specific TFDP3 causes male infertility with oligoasthenoteratozoospermia in humans and cynomolgus monkeys - Chunyu Liu; Chaofeng Tu; Peng Li; Huan Wu; Feng Wan; Yong Lu; Shuyan Tang; Xin Li; Kuokuo Li; Jiaxiong Wang; Yang Gao; Xinyan Geng; et al. (Science China Life Sciences, 2026)

Orderly regulation of amine-functionalized mesoporous silica SBA-15 to enhance the rapid adsorption and desorption of CO₂ - Leyu Nie; Yu Cheng; Wenqing An; Mingxuan Ren; Yiling Xu; Kai Xia; Zhaojun Chen; Deshuai Sun (Journal of Environmental Chemical Engineering, 2026)

Cu-doped OMS-2 catalysts for photothermal synergistic VOCs segradation: Efficiency enhancement under UV-Vis irradiation in flow conditions - Yunchao Liu; Xinyu Qi; Xiang Bai; Yuanli Lu; Jing Sun; Chen Wang; Tingting Shen; Hao Liu; Yanyan Liu; Jiaqi Zhao; Tianyu Ji; Ruobing Liu; et al. (Journal of Environmental Sciences, 2026)

Defective modulation of bio-base metal-organic frameworks for enhanced CO2 adsorption and catalytic conversion - Yiling Xu; Cong Liu; Leyu Nie; Xinru Liu; Kai Xia; Zhaojun Chen; Deshuai Sun (Journal of Environmental Chemical Engineering, 2025)

Tannic acid: A star molecule in the construction and biomedical applications of hydrogels - Wei Zhang; Yiling Chen; Jing Huang; Ziyi Xiao; Fangjing Wang; Guihui Zhu; Xinying Liao; Yuxin Tang; Zhihao Song; Jian Sun; Yang Liu (Chemical Engineering Journal, 2025)

Persulfate activation by biochar for trace organic contaminant removal from urban stormwater - Yiling Zhuang; Stefan B. Haderlein; Holger V. Lutze; Chen Sun; Friedrich Fink; Andrea Paul; Stephanie Spahr (Water Research, 2025)

A new framework for evaluating land suitability for Goji (Lycium barbarum L.) cultivation across China - Yunpeng Hong; Yiling Chen; Yanyan Su; Gangqiang Dong; Xiaodong Song; Jing Zhang; Han Wang; Zhongxiu Sun; Long Guo; Jinling Yang; Ganlin Zhang (Journal of Environmental Management, 2025)

Structure characterization and biological activity of polysaccharides from Trametes sanguinea (TS-P) and wild Lentinus edodes (LE-P) - Ke Liu; Zheng-ao Sun; Xinlin Li; Xin Qing; Wen Yu; Mengnan Liu; Xiang Ding; Yiling Hou (Food Bioscience, 2025)

HTBPPS: A high-throughput behavioral phenotyping platform for shrimp - Wenzhi Cheng; Huimin Peng; Chuanxi Chen; Heqian Zhang; Yiming Wei; Jinqian Yang; Xiaojie Deng; Yiling Hou; Siqi Li; Tingting Huang; Yougen Chen; Chichi Liu; et al. (Aquaculture, 2025)

Address the challenge of cultivated land abandonment by cultivated land adoption: An evolutionary game perspective - Yong Sun; Yiling Miao; Zhiju Xie; Xingling Jiang (Land Use Policy, 2025)

Cradle-to-gate GHG emissions and decarbonization potentials of minivan-equipped hydrogen fuel cell system - Yiling Xiong; Fang Wang; Dongchang Zhao; Xin Sun; Fengfeng Ren; Mingnan Zhao; Jingshu Hao; Ye Wu; Shaojun Zhang (Resources, Conservation and Recycling, 2025)

Drivers and barriers to digital transformation in agriculture: An evolutionary game analysis based on the experience of China - Yong Sun; Yiling Miao; Zhiju Xie; Runtian Wu (Agricultural Systems, 2024)

Seasonal variation of antioxidant bioactive compounds in southern highbush blueberry leaves and non-destructive quality prediction in situ by a portable near-infrared spectrometer - Jianbo Qi; Shuai Sun; Liuqiang Zhang; Yilin Zhu; Huiji Zhou; Xiaona Gan; Bo Li; Yiling Chen; Wei Li; Tingzhao Li; Yiming Li; Gangqiang Dong; et al. (Food Chemistry, 2024)

GMPR2-MDA5 interaction bridged the cell junction and anti-GCRV immune - Mingxue Sun; Yiling Li; Hao Tang; Wei Duan; Yijing Liao; Tiaoyi Xiao; Yaoguo Li (Aquaculture, 2024)

LC–MS and MALDI–MSI-based metabolomic approaches provide insights into the spatial–temporal metabolite profiles of Tartary buckwheat achene development - Tingxia Liu; Peng Wang; Yiling Chen; Boshi Sun; Qing Li; Huihua Wan; Wei Yang; Pengda Ma; Dong Zhang; Gangqiang Dong; Shilin Chen; Qingfu Chen; et al. (Food Chemistry, 2024)

Chiral Au nanostars for SERS sensing of enantiomers discrimination, multibacteria recognition and photothermal antibacterial application - Xueqin Huang; Qiuxia Chen; Yiling Ma; Chan Huang; Weixia Zhi; Jiahao Li; Runmin Zeng; Jiang Pi; Jun-fa Xu; Jun Xu; Wanyong Yang; Jianglin Zhang; et al. (Chemical Engineering Journal, 2024)

Structures, issues, and optimization strategies of Ni-rich and Co-low cathode materials for lithium-ion battery - Honggui Xie; Huarong Peng; Dongting Jiang; Zhe Xiao; Xueping Liu; Hao Liang; Mingli Wu; Dongming Liu; Yun Li; Yiling Sun; Shengkui Zhong; Zhengfang Qian; et al. (Chemical Engineering Journal, 2023)

Metatranscriptome deciphers the effects of non-antibiotic antimicrobial agents on antibiotic resistance and virulence factors in freshwater microcosms - Yan Wang; Kepin Ni; Zhenyan Zhang; Nuohan Xu; Chaotang Lei; Bingfeng Chen; Qi Zhang; Liwei Sun; Yiling Chen; Tao Lu; Haifeng Qian (Aquatic Toxicology, 2023)

More profound impact of CP ENSO on Australian spring rainfall in recent decades - Yiling Ma; Jilin Sun; Tianyun Dong; Weidong Yu; Wenjie Dong (Climate Dynamics, 2023)
Most of Australia was in severe drought from 2018 to early 2020. Here we link this drought to the Pacific and Indian Ocean sea surface temperature (SST) modes associated with Central Pacific (CP) El Niño–Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD). Over the last 20 years, the occurrence frequency of CP El Niño has increased. This study extends the previous understanding of eastern Pacific (EP) El Niño-Australian rainfall teleconnections, exhibiting that CP El Niño can bring much broader and stronger rainfall deficiencies than EP El Niño during austral spring (September–November) over the northern Australia (NAU), central inland Australia and eastern Australia (EAU). The correlations between SST fields and rainfall in three Cluster regions divided by clustering analysis also confirm this, with rainfall variability in most of Australia except southern Australia (SAU) most significantly driven by CP ENSO. Also, we demonstrate that the CP El Niño affects rainfall in extratropical EAU via the Pacific-South American (PSA) pattern. While the influence of EP El Niño is only confined in tropical NAU because its PSA pattern sits far too east to convey its variability. With the development of ENSO diversity since 2000, the footprint of El Niño on Australian rainfall has become more complex.

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Geographic distribution pattern and ecological niche differentiation of endangered Opisthopappus in Taihang Mountains - Li Liu; Hao Zhang; En Zang; Qiyang Qie; Shan He; Weili Hao; Yafei Lan; Zhixia Liu; Genlou Sun; Yiling Wang (Brazilian Journal of Botany, 2023)

Challenging the limits of the oxygen balance of a pyrazole ring - Wenjin Zhang; Yiling Yang; Yuchuan Wang; Teng Fei; Yu Wang; Chenghui Sun; Siping Pang (Chemical Engineering Journal, 2023)

Use of DNA nanosensors based on upconverting nanoparticles for detection of Nosema bombycis by fluorescence resonance energy transfer - Ping He; Hongli Chen; Jiancheng Sun; Qiang Wang; Xudong Tang; Yiling Zhang; Feng Zhu; Zhongyuan Shen (Folia Microbiologica, 2022)

Isolation and identification of two Serratia marcescens strains from silkworm, Bombyx mori - Yiling Zhang; Ruisha Shang; Jiao Zhang; Junhao Li; Guanyu Zhu; Mingshuai Yao; Jiancheng Sun; Zhongyuan Shen (Antonie van Leeuwenhoek, 2020)

Soil Properties and Microbial Diversity at the Frontier of Laohugou Glacier Retreat in Qilian Mountains - Yajie Zhu; Yiling Zhang; Huiying Chen; Yaqi Wang; Fuqian Cao; Weijun Sun; Xiaoyu Qi; Yucui Zhao; Fei Xu (Current Microbiology, 2020)

Immunization with an adenovirus-vectored TB vaccine containing Ag85A-Mtb32 effectively alleviates allergic asthma - Yiling Zhang; Ying Feng; Liang Li; Xianmiao Ye; Jinlin Wang; Qian Wang; Pingchao Li; Na Li; Xuehua Zheng; Xiang Gao; Chufang Li; Feng Li; et al. (Journal of Molecular Medicine, 2018)